High‐Rate Aqueous Aluminum‐Ion Batteries Enabled by Confined Iodine Conversion Chemistry. Issue 10 (5th September 2021) - Yang, Shuo; Li, Chuan; Lv, Haiming; Guo, Xun; Wang, Yanbo; Han, Cuiping; Zhi, Chunyi; Li, Hongfei
Abstract: Most reported cathode materials for rechargeable aqueous Al metal batteries are based on an intercalative‐type chemistry mechanism. Herein, iodine embedded in MOF‐derived N‐doped microporous carbon polyhedrons (I2 @ZIF‐8‐C) is proposed to be a conversion‐type cathode material for aqueous aluminum‐ion batteries based on "water‐in‐salt" electrolytes. Compared with the conventional Al–I2 battery using ionic liquid electrolyte, the proposed aqueous Al–I2 battery delivers much enhanced electrochemical performance in terms of specific capacity and voltage plateaus. Benefitting from the confined liquid–solid conversion of iodine in hierarchical N‐doped microporous carbon polyhedrons and enhanced reaction kinetics of aqueous electrolytes, the I2 @ZIF‐8‐C electrode delivers high reversibility, superior specific capacity (≈219.8 mAh g −1 at 2 A g −1 ), and high rate performance (≈102.6 mAh g −1 at 8 A g −1 ). The reversible reaction between I2 and I −, with I3 − and I5 − as intermediates, is confirmed via ex situ Raman spectra and X‐ray photoelectron spectroscopy. Furthermore, solid‐state hydrogel electrolyte is employed to fabricate a flexible Al–I2 battery, which shows performance comparable to batteries using liquid electrolyte and can be integrated to power wearable devices as a reliable energy supply. Abstract : Confining iodine species into MOF‐derived carbon polyhedron can provide higher thermal stability and confined solid–liquid conversion reactions. As a result, aqueous Al–I2 batteries deliver high reversibility, superior specific capacity, and high rate performance. This work may open avenues for the further exploration of conversion‐type cathode materials for aqueous Al batteries.